Pengaruh Ulasan Produk dan Layanan Purna Jual terhadap Minat Beli Ulang Smartphone Xiaomi Redmi Note 11 (Survei pada Komunitas Pengguna Xiaomi Redmi Note 11) - Arya Ananda; Ajat Sudrajat (Peneliti.net, 2022)
This study aims to determine, analyze, and explain the effect of Product Reviews and After-Sales Service on Repurchase Intention of Xiaomi Redmi Note 11 Smartphone. This study uses quantitative methods with descriptive and verification approaches. The population used is the Xiaomi Redmi Note 11 smartphone user community on Facebook which consists of 4,020 people. The number of samples is determined by using the Slovin 5% formula so that the number of samples is 364 respondents. The sampling technique used was purposive sampling. The analytical techniques used are scale range analysis and path analysis with the help of the Method of Successive Interval (MSI), Microsoft Excel 2019 software, and IBM SPSS 20. The results of the descriptive study indicate that the variables of Product Reviews, After Sales Service, and Repurchase Intention are in the Good category. While the results of the verification research, it is known that the correlation coefficient between Product Reviews and After-Sales Service is 0.648 which indicates that the two have a strong relationship. The partial effect of Product Reviews on Repurchase Intention is 16.1%, while the partial effect of After-Sales Services on Repurchase Intention is 34.7%. The effect of Product Reviews and After-Sales Services on Repurchase Intention simultaneously is 50.8%, while the remaining 49.2% is influenced by variables that do not exist in this study.